If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(a + 2) = 9 Reorder the terms: 6 + -1(2 + a) = 9 6 + (2 * -1 + a * -1) = 9 6 + (-2 + -1a) = 9 Combine like terms: 6 + -2 = 4 4 + -1a = 9 Solving 4 + -1a = 9 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1a = 9 + -4 Combine like terms: 4 + -4 = 0 0 + -1a = 9 + -4 -1a = 9 + -4 Combine like terms: 9 + -4 = 5 -1a = 5 Divide each side by '-1'. a = -5 Simplifying a = -5
| -8-3x=2x+13 | | C=8/7(k-26) | | 2x+4=2(4x-3)-3(-8+4x) | | 0.2(x-2)+0.5(x+5)=0 | | x^2/3x-5=0 | | 7(2x-4)=8 | | 5b+7=-23 | | X+45=-5y | | 8+12x=52x+x | | 3+6y=13+6z | | 83-4=8x+23 | | 3x-5=3+8-x | | 1/11y^-4 | | (4+3x)+x=36 | | -7/x+2=-4-3/x-3 | | xy+3x=2 | | 5ab+5c=10b-4ac | | -81=-(x-7)-15 | | 3x-5=(x+1) | | 5y+3-1xy=2x+8y-5 | | -7x+9=-40 | | (4_11/4:19/16).(_155/8)= | | 3x+9=-40 | | 87-2x=43x+22 | | 5(w-3)=w-11 | | P=3n | | 5p=6p+12 | | 62-3x=8x+15 | | 19a-7-17a+23=-14 | | 14=7x+4-5x | | 5x+9=58x-2 | | 5-0.03x=0.2-0.05x |